Penentuan Mahar Menggunakan Emas dalam Tinjauan Hukum Adat di Kecamatan Indrajaya Kabupaten Pidie - Isma Zaiyanna; Muhammad Yunus; Yusrijal Abdar; Rizal Fahmi; Ridayani Ridayani (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Marriage dowry in Indrajaya Subdistrict, Pidie Regency, is generally standardized in the form of pure gold, which is in line with local culture and customary law, reflecting the strong influence of traditions passed down from generation to generation. This study aims to (1) describe the determination of dowry in the form of gold based on customary law and (2) explain the customary provisions or agreements governing the standard of gold dowry in Indrajaya Subdistrict, Pidie Regency. This research employed a qualitative approach with a descriptive design, and data were collected through in-depth interviews with fifteen informants consisting of five keuchik (village heads), five imum meunasah (religious leaders), and five tuha peut (customary elders). The findings indicate that the community in Indrajaya Subdistrict consistently uses gold as dowry in marriage ceremonies and that no substitution with other forms of dowry has ever been found. The use of gold is understood as a symbol of sincerity, honor, and respect for the bride, as well as an effort to preserve local traditions. The determination of the dowry amount is conducted through a structured family deliberation process, beginning with internal discussions within each family. This study concludes that dowry determination in Indrajaya Subdistrict is carried out through family deliberation with gold as the only socially accepted form of dowry and without written sanctions for deviations, and therefore recommends that customary agreements on dowry standards be formally documented and that future research adopt a comparative approach with other subdistricts in Pidie Regency.